The Effects of Abscisic Acid Administration in PCOS Rat Model and H2O2-Induced Human Granulosa Cell Damage: A Preliminary Investigation - Yidong Xie; Junliang Guo; Yifan Zhao; Xiaohong Li; Li Xiao; Shangwei Li (IMR Press, 2023)
Background: Polycystic ovary syndrome (PCOS) is commonly associated with metabolic disorders. Abscisic acid (ABA), a plant hormone found in vegetables and fruits that can be naturally supplied through dietary intake, has previously been studied for its benefits to human health, particularly in people with diabetes. ABA plays a key role in glucose metabolism, inflammation, and tumor growth. The aim of this study was to investigate the therapeutic effect of ABA on letrozole-induced PCOS rats. Methods: Wistar rats were implanted with continuous-release letrozole pellets to induce a PCOS-like phenotype, and subsequently treated with ABA or vehicle control. Body weight changes, Testosterone (T) levels, fasting insulin measurements, and glucose tolerance tests were investigated. A cell apoptosis model, induced by hydrogen peroxide (H2O2), was established. Cell viability was tested by cell counting Kit-8. Cell apoptosis was tested by flow cytometry, and oxidative stress state of cells was examined via reactive oxygen species (ROS) array. Results: Body weight, glucose impairment, and T level were significantly improved in ABA-treated PCOS rats compared to vehicle-treated rats. ABA significantly reduced H2O2-induced human ovarian granulosa cell line (KGN) cell apoptosis and ROS levels and increased cell viability. Conclusions: The findings suggest that ABA could be an adjunctive treatment candidate for improving the insulin sensitivity and hyperandrogenemia of PCOS patients, and for ameliorating H2O2-induced cell apoptosis and oxidative stress.